2015
DOI: 10.1016/j.canlet.2015.05.004
|View full text |Cite|
|
Sign up to set email alerts
|

The development of cisplatin resistance in neuroblastoma is accompanied by epithelial to mesenchymal transition in vitro

Abstract: Neuroblastoma is a challenging childhood malignancy, with a very high percentage of patients relapsing following acquisition of drug resistance, thereby necessitating the identification of mechanisms of drug resistance as well as new biological targets contributing to the aggressive pathogenicity of the disease. In order to investigate the molecular pathways that are involved with drug resistance in neuroblastoma, we have developed and characterised cisplatin resistant sublines SK-N-ASCis24, KellyCis83 and CHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 60 publications
5
66
1
Order By: Relevance
“…Importantly, we found no change in gene expression of Vimentin , a hallmark in cells undergoing EMT (high Vimentin and low E-cadherin expression) [37]. A number of other genes involved in EMT in neuroblastoma, such as ACTN4 , MYH9 , ROCK1 and TCF3 [38, 39], failed to show any significant changes in our studies. Finally, we did not observe obvious cell morphological changes 72 hours after transient overexpression of TFAP4 .…”
Section: Discussioncontrasting
confidence: 52%
“…Importantly, we found no change in gene expression of Vimentin , a hallmark in cells undergoing EMT (high Vimentin and low E-cadherin expression) [37]. A number of other genes involved in EMT in neuroblastoma, such as ACTN4 , MYH9 , ROCK1 and TCF3 [38, 39], failed to show any significant changes in our studies. Finally, we did not observe obvious cell morphological changes 72 hours after transient overexpression of TFAP4 .…”
Section: Discussioncontrasting
confidence: 52%
“…showed that cellular surface changed remarkably after drug stimulations and the change of stimulation conditions (the addition of Rtx, the increase of stimulation concentration, the increase of stimulation time) could result in more significantly morphological alterations on the cells (e.g., distinct particles and pores occurred on the cell surface, cellular shape became irregular, cellular nuclei were discerned). Traditional studies for investigating the anticancer effects of chemotherapy drugs or monoclonal antibodies were commonly based on the ensemble results on a large number of cells by using various biochemical methods [26]- [28], e.g., flow cytometry, western immunoblotting, polymerase chain reaction (PCR), and proliferation/death assays. The flaw of these studies was that they cannot reveal the nanoscale situations taking place on single cells during the process of drug actions.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular physiological activities are dynamic essentially. However, traditional biochemical methods (such as fluorescence, western immunoblotting, and PCR) destroy the natural structures of cells (e.g., labeling, staining, and lysis) [26]- [28], meaning that we cannot dynamically monitor the changes of cellular physiological parameters. Cellular surface roughness and mechanics detected by AFM are label free, and, thus, we can real-time monitor their dynamic changes on single cells, which can provide novel insights into our understanding of the dynamical cellular activities.…”
Section: Resultsmentioning
confidence: 99%
“…In NB, general EMT pathways have been associated with the development of drug resistance and correlate with lower overall survival. In an analysis of cisplatin resistant human NB cell lines, CHP-212Cis100, KellyCis83, and SK-N-ASCis24, all resistant lines compared to their cisplatin-sensitive counterparts were found to be enriched in gene pathways of a mesenchymal phenotype, including actin cytoskeleton signaling, integrin-linked kinase signaling, and epithelial adherens junction signaling (Piskareva, et al, 2015). In a similar analysis, SK-N-SH and SK-N-BE doxorubicin resistant cell lines had enriched expression of genes associated with epithelial to mesenchymal transition and had a more invasive phenotype as compared to their parenteral strains (Naiditch, et al, 2015).…”
Section: Neural Crest Development and Nbmentioning
confidence: 99%